An Internet scale simulation setup for BGP. - Hao, Fang
BGP convergence issues in the Internet have been extensively studied in recent years. It has been shown through formal analysis that BGP convergence is not always guaranteed. When it does converge, active measurement based techniques have determined that the convergence process may take upto 15 minutes while also causing intermittent packet loss/latency. As BGP enhancements are explored to address this convergence problem, controlled simulation experiments offer the most convenient and feasible mechanism to compare the efficacy of enhanced BGP procedures with respect to the current protocol mechanisms. Since the convergence behavior can be significantly influenced by network topology, it is desirable to use large Internet like topologies in such controlled simulations.In this paper, we present first steps towards realizing a large scale BGP simulation environment for reasoning about current BGP procedures and also for evaluating the efficacy of BGP protocol enhancements.